PERGESERAN SEKTOR EKONOMI UNGGULAN KABUPATEN BANTUL PASCA GEMPA MELALUI ANALISIS TIPOLOGI KLASSEN - Suprayitno, Bambang; Nurseto, Tejo (JEJAK: Jurnal Ekonomi dan Kebijakan, 2011)
This study aims at knowing whether there are changes in superrior and potential sector in Kabupaten Bantul after the earthquake and identifying the sectors that become the superior and potential sector before and after the earthquake. The data were secondary data of PDRB based on business sector and labor in Bantul, started from 2003 up to 2008. Klassen typology is used for meassuring and classifying the data. The finding show that before the earthquake the superior and potential sectors are electricity, gas, water, financial rent and company service, and transportation and communication. Then, after the earthquake those sectors still become superior and potential, but there is a new sector that become superior too. It is infrastructure